2017
DOI: 10.1038/srep45740
|View full text |Cite
|
Sign up to set email alerts
|

Calcium oxalate crystals and oxalate induce an epithelial-to-mesenchymal transition in the proximal tubular epithelial cells: Contribution to oxalate kidney injury

Abstract: TGF-β1 is the main mediator of epithelial-to-mesenchymal transition (EMT). Hyperoxaluria induces crystalluria, interstitial fibrosis, and progressive renal failure. This study analyzed whether hyperoxaluria is associated with TGF-β1 production and kidney fibrosis in mice and if oxalate or calcium oxalate (CaOx) could induce EMT in proximal tubule cells (HK2) and therefore contribute to the fibrotic process. Hyperoxaluria was induced by adding hydroxyproline and ethylene glycol to the mice’s drinking water for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 40 publications
1
49
0
3
Order By: Relevance
“…TNF receptor and TGF beta signaling pathways are assumed to play a role in the induction of an immune response in CaOx nephropathies. [ 35,36 ] Indeed, we found elevated expression of TNF alpha and TGF beta signaling pathway genes, such as TNF receptor superfamily member 10a, TNF alpha induced protein 3, and TGF beta receptor 3, in the CaOx group compared to all other groups (Figure 5C). Further, cell surface glycoproteins, in particular annexin II, were reported to be upregulated in hyperoxaluric animal models and suggested to facilitate CaOx adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…TNF receptor and TGF beta signaling pathways are assumed to play a role in the induction of an immune response in CaOx nephropathies. [ 35,36 ] Indeed, we found elevated expression of TNF alpha and TGF beta signaling pathway genes, such as TNF receptor superfamily member 10a, TNF alpha induced protein 3, and TGF beta receptor 3, in the CaOx group compared to all other groups (Figure 5C). Further, cell surface glycoproteins, in particular annexin II, were reported to be upregulated in hyperoxaluric animal models and suggested to facilitate CaOx adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of the epithelial mesenchymal transition of tubular cells and renal fibrogenesis induced by oxalate crystals has been demonstrated by multiple studies in mouse, rat, and cell models (Toblli et al, 2002 ; Convento et al, 2017 ). As our previous study showed, the expression of kidney interstitial markers (α-SMA and Vim) increased gradually in response to the glyoxylate-induced CaOx crystal formation and deposition (Hu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 98%
“…Вони набувають характеристики, які притаманні мезенхімальним клітинам, а саме -негативну регуляцію кадгерином, цитокератином, що призводить до втрати клітинних контактів. Навпаки, позитивну регуляцію мезенхімальних клітин під час епітеліально-мезенхімального переходу здійснюють віментин і α-актин [62].…”
Section: таблиця 2 продукти з високим вмістом оксалатівunclassified
“…Експресія BMP-7 виявлена в первинних клітинах ураження: епітеліальних клітинах та подоцитах. Вона істотно зменшується під час гострого ураження нирок, а введення екзогенного аналога прискорює відновлення ренальних пошкоджень [62].…”
Section: таблиця 2 продукти з високим вмістом оксалатівunclassified